ANALISIS PERSEPSI HARGA, MEMBERSHIP CARD, DAN SERVICE PERFORMANCE TERHADAP KEPUTUSAN PEMBELIAN DI LOTTE MART SURAKARTA - Heri Agus Setiawan; Ida Aryati DPW; Burhanudin Burhanudin (JURNAL ILMIAH EDUNOMIKA, 2019)
This study aims to determine the effect of perception price, membership card and service performance on purchasing decisions at Lotte Mart Surakarta. This type of research uses descriptive quantitative methods. The population of this study is consumers who buy product at Lotte Mart Surakarta whose numbers are not infinite. The sample in the study amounted to 100 people with the sampling technique using non probability. Sampling is the accidental sampling method, method of collecting data by distributing questionnaires. Technique of data analysis in the contents of this study using multiple linier regression, t test, F test, coefficient of determination. The results of the analysis show that the results of the F test show that there ia a simultaneous influence between perceived price, membership card and service performance on purchasing decisions at Lotte Mart Surakarta. Based on the t test in this study shows that the perceptions price has a positive and significant effect on purchasing decisions at Lotte Mart Surakarta. Membership card has a positive and significant effect on purcashing decisions at Lotte Mart Surakarta. Service performance has a positive and significant effect on purchasing decisions at Lotte Mart Surakarta. The coefficientof purchasing descisions perceptions price, membership card, and service performance have an effect of 0,54% on purchasing descisions at Lotte Mart Surakarta. Keyword: Perception Price, Membership Card, Service Performance, Purchasing Decision